Rheumatoid arthritis: what do MRI and ultrasound show - Iwona Sudoł-Szopińska; Lennart Jans; James Teh (Journal of Ultrasonography, 2017)
Rheumatoid arthritis is the most common inflammatory arthritis, affecting approximately 1% of the world’s population. Its pathogenesis has not been completely understood. However, there is evidence that the disease may involve synovial joints, subchondral bone marrow as well as intra- and extraarticular fat tissue, and may lead to progressive joint destruction and disability. Over the last two decades, significant improvement in its prognosis has been achieved owing to new strategies for disease management, the emergence of new biologic therapies and better utilization of conventional disease-modifying antirheumatic drugs. Prompt diagnosis and appropriate therapy have been recognized as essential for improving clinical outcomes in patients with early rheumatoid arthritis. Despite the potential of ultrasonography and magnetic resonance imaging to visualize all tissues typically involved in the pathogenesis of rheumatoid arthritis, the diagnosis of early disease remains difficult due to limited specificity of findings. This paper summarizes the pathogenesis phenomena of rheumatoid arthritis and describes rheumatoid arthritis-related features of the disease within the synovium, subchondral bone marrow and articular fat tissue on MRI and ultrasound. Moreover, the paper aims to illustrate the significance of MRI and ultrasound findings in rheumatoid arthritis in the diagnosis of subclinical and early inflammation, and the importance of MRI and US in the follow-up and establishing remission. Finally, we also discuss MRI of the spine in rheumatoid arthritis, which may help assess the presence of active inflammation and complications.